2014
DOI: 10.1007/s11596-014-1308-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor agonist dexamethasone attenuates renal ischemia/reperfusion injury by up-regulating eNOS/iNOS

Abstract: The aim of this study was to determine the effect of dexamethasone (DEX) on renal ischemia/reperfusion injury (IRI). C57BL/6 mice were randomly divided into Sham group, IRI group and DEX group. The mice in IRI and DEX groups subjected to renal ischemia for 60 min, were treated with saline or DEX (4 mg/kg, i.p.) 60 min prior to I/R. After 24 h of reperfusion, the renal function, renal pathological changes, activation of extracellular signal-regulated kinase (ERK) and glucocorticoid receptor (GR), and the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In normal kidney tissues, endothelial NOS is predominantly expressed in the renal blood vessels and capillaries; neuronal NOS is predominantly expressed in the juxtaglomerular macula densa; and iNOS is expressed in the renal medullary thick ascending limb, proximal tubule, distal convoluted tubule and interlobular arteries, arcuate arteries and blood vessels, and other areas of the glomerulus (31). Under a pathophysiological state, iNOS exhibits high levels of expression in mesangial cells, epithelial cells, smooth muscle cells and renal tubular epithelial cells, and there are high levels of infiltrated inflammatory cells, including in the glomeruli and renal interstitium (32). The present study showed that honokiol significantly decreased the gene expression and activity of iNOS in the IRI rats.…”
Section: Discussionmentioning
confidence: 99%
“…In normal kidney tissues, endothelial NOS is predominantly expressed in the renal blood vessels and capillaries; neuronal NOS is predominantly expressed in the juxtaglomerular macula densa; and iNOS is expressed in the renal medullary thick ascending limb, proximal tubule, distal convoluted tubule and interlobular arteries, arcuate arteries and blood vessels, and other areas of the glomerulus (31). Under a pathophysiological state, iNOS exhibits high levels of expression in mesangial cells, epithelial cells, smooth muscle cells and renal tubular epithelial cells, and there are high levels of infiltrated inflammatory cells, including in the glomeruli and renal interstitium (32). The present study showed that honokiol significantly decreased the gene expression and activity of iNOS in the IRI rats.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the above, attenuation of inflammation after acute ischemic kidney injury may be a suitable therapeutic strategy in the attenuation or prevention of progressive renal injury. Dexamethasone is a glucocorticoid, widely used in renal diseases as an anti-inflammatory and immunosuppressive agent [ 8 ]. Corticosteroids inhibit the synthesis of chemokines and cytokines resulting in protection against inflammation, and at high doses inhibit the immune response [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown in experimental models that dexamethasone has a protective effect against ischemic damage in liver and hart [ 10 , 11 ]. In the kidney, pre-treatment with dexamethasone has been demonstrated to ameliorate the severity of an acute ischemic insult [ 8 ]. These studies, however, particularly covered the acute injury phase up to 24 h after the ischemic insult.…”
Section: Introductionmentioning
confidence: 99%
“…blood supply to an organ, in which the arterial blood supply shortens and led to a severe imbalance of metabolic supply and demand that causes tissue hypoxia [2][3][4][5][6][7][8]; however, reperfusion is commonly used to re-establish reoxygenation and the restoration of blood flow, exacerbate renal tissue injury and dysfunction, and initiate profound inflammatory response [9]. The pathogenesis of AKI is complex; an excessive and inflammation response [10][11][12] has been elucidated as the key mechanisms of renal ischemia/ reperfusion injury.…”
mentioning
confidence: 99%